Moral Disengagement and Risk Prototypes in the Context of Adolescent Cyberbullying: Findings From Two Countries - Lazuras, Lambros; Brighi, Antonella; Barkoukis, Vassilis; Guarini, Annalisa; Tsorbatzoudis, Haralambos; Genta, Maria Luisa (Frontiers in Psychology, 2019)
Cyberbullying is associated with a wide range of mental health difficulties and behavioural problems in adolescents and research is needed to better understand psychological correlates of this behaviour. The present study used a novel model that incorporated Social Cognitive Theory and the Prototype/Willingness Model to identify the correlates of behavioural willingness to engage in cyberbullying in two countries. Adolescent students were randomly selected from secondary schools in Italy (n = 1710) and Greece (n = 355), and completed anonymous measures of moral disengagement, descriptive norms, risk prototype evaluations and behavioural willingness to engage in cyberbullying. Hierarchical linear regression analyses showed that willingness to engage in cyberbullying was associated with moral disengagement, prototype evaluations and descriptive social norms in Italy, and with gender, moral disengagement and moral disengagement in Greece. Regression-based multiple mediation modelling further showed that association between moral disengagement and cyberbullying willingness was mediated by prototype evaluations in Italy and by descriptive norms in Greece. The implications of our findings are discussed in the context of understanding the self-regulating cyberbullying perpetration in adolescents and school-based policies and interventions to prevent cyberbullying behaviour.